2021
DOI: 10.3390/ma14030662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Naphthalene-Based Superplasticizer and Polycarboxylic Acid Superplasticizer on the Properties of Sulfoaluminate Cement

Abstract: In order to study what the effect of superplasticizers on the setting time, fluidity and compressive strength of calcium sulfoaluminate cement (CSA) a naphthalene-based superplasticizer (BNS) and a polycarboxylic acid superplasticizer (PC) were selected to interact with CSA pastes and ye’elimite, respectively. X-ray diffraction (XRD), thermogravimetric (TG) analysis and scanning electron microscopy (SEM) analytical methods were used to investigate the class, amount and microstructure of the CSA pastes and ye’e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…However, the high fluidity they caused could provide adverse effects, such as bleeding and phase separation. In order to eliminate these drawbacks of superplasticizers, the addition of viscosity-enhancing compounds was developed [ 41 , 42 ].…”
Section: Plasticizers and Superplasticizersmentioning
confidence: 99%
“…However, the high fluidity they caused could provide adverse effects, such as bleeding and phase separation. In order to eliminate these drawbacks of superplasticizers, the addition of viscosity-enhancing compounds was developed [ 41 , 42 ].…”
Section: Plasticizers and Superplasticizersmentioning
confidence: 99%
“…The hydration rate of anhydrous calcium sulphoaluminate (C 4 A 3 S) is shown in Equation ( 4), and its hydration rate is extremely fast, which can make the 1 d strength of high-belite sulphoaluminate cement reach more than 85% of the final strength [31,34]. As can be seen from Figure 5, the content of hydrated calcium sulphoaluminate increases with the increase in nanosilica content at the same cement age, which also indicates that nanosilica can further promote the hydration process of anhydrous calcium sulphoaluminate (C 4 A 3 S).…”
Section: Xrd Analysismentioning
confidence: 99%
“…2-acrylamide-2-methacrylic acid (AMPS) can be used as a monomer for PCE to achieve good clay resistance, because of its acylamino group and sulfonic group [13]. Wu et al found that the introduction of AMPS to the structure of PCE was beneficial to the clay resistance [14]. Nevertheless, owing to its poor calcium complexing ability, the slump loss of concrete would be serious.…”
Section: Introductionmentioning
confidence: 99%